2017
DOI: 10.1016/j.eswa.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Multi-view fuzzy clustering with minimax optimization for effective clustering of data from multiple sources

Abstract: Multi-view data clustering refers to categorizing a data set by making good use of related information from multiple representations of the data. It becomes important nowadays because more and more data can be collected in a variety of ways, in different settings and from different sources, so each data set can be represented by different sets of features to form different views of it. Many approaches have been proposed to improve clustering performance by exploring and integrating heterogeneous information un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…The aggregation and splitting procedures presented hereafter are respectively based on the minimization of a criterion that is inspired by the one used in the multi-view fuzzy K-means algorithm (Wang and Chen, 2017):…”
Section: Framework and Data Scalingmentioning
confidence: 99%
“…The aggregation and splitting procedures presented hereafter are respectively based on the minimization of a criterion that is inspired by the one used in the multi-view fuzzy K-means algorithm (Wang and Chen, 2017):…”
Section: Framework and Data Scalingmentioning
confidence: 99%
“…The expectation‐maximization (EM) algorithm is a statistical analysis of the probability approach, which performs the clustering operation based on cluster center initialization . The fuzzy K‐means (FKM) algorithm is mostly employed for medical image segmentation . Aparajeeta et al suggested a possibilistic based fuzzy approach that supports the eradication of noise levels in the segmentation results.…”
Section: Related Workmentioning
confidence: 99%
“…18 The fuzzy K-means (FKM) algorithm is mostly employed for medical image segmentation. 19 Aparajeeta et al 20 suggested a possibilistic based fuzzy approach that supports the eradication of noise levels in the segmentation results. The performance of the process using the spatial information of the nearest pixels is to enhance the brain image segmentation.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations